Creep behavior and durability of concrete elements strengthened with NSM CFRP strips - Silva, Patrícia (2014)
This paper presents an experimental program aimed to better understand durability and long-term deformational performance of concrete structures strengthened with the near-surface mounted (NSM) technique. The conducted experiments include beam pullout specimens and slabs. Both types of specimens were submitted to sustained loads under the following environmental conditions: (i) placed in the laboratory premises; (ii) immersed in a water tank at 20ºC with 0% of chlorides; (iii) immersed in a water tank at 20ºC with 3.5% of chlorides; (iv) submitted to wet/dry cycles at 20ºC with 3.5% of chlorides. The mid-span vertical deflection of the slabs was continuously monitored, whereas the beam pullout specimens had their loaded end slip monitored. Creep, degradation and their relation with temperature were some of the observations pointed out. The effect of creep is practically negligible in the beam pull out tests and the evolution of the loaded end slip was mainly controlled by the environmental temperature at the lab. Nonetheless, the slabs have a pronounced creep effect, despite it has been mitigated when the slabs were submitted in water. The paper presents the general description of the experimental program and the first results pertaining to sustained loadings until ages up 439 days (current state of the process).